Spanish version of the Inferential Confusion Questionnaire‐Expanded Version: Further support for the role of inferential confusion in obsessive–compulsive symptoms. (3rd March 2020) - Llorens‐Aguilar, Sara; García‐Soriano, Gemma; Roncero, María; Barrada, Juan Ramón; Aardema, Frederick; O Connor, Kieron
Abstract : The purposes of this research were (1) to analyse the psychometric properties of the Inferential Confusion Questionnaire‐Expanded Version (ICQ‐EV) in a Spanish population; (2) to explore the role of inferential confusion in obsessive–compulsive disorder (OCD); and (3) to compare the inferential confusion construct in nonclinical and clinical samples. A sample of 342 nonclinical participants and 66 patients with OCD completed the ICQ‐EV Spanish adaptation as well as a set of questionnaires. Results confirmed a good fit of the ICQ‐EV Spanish version to the original unifactorial structure and excellent internal consistency and test–retest reliability. Moreover, results confirmed that the ICQ‐EV predicts Obsessing, Checking, Washing, and Hoarding symptoms, independently of the contribution of dysfunctional beliefs. In addition, OCD patients scored significantly higher on the ICQ‐EV than nonclinical participants. The Spanish version of the ICQ‐EV is a reliable instrument to assess inferential confusion, and further support is provided for the relevance of the inferential confusion construct in OCD.